Improving the anti-tumor immune responses against cancer cells - Sousa, Diana Isabel Pacheco de (2016)
Cancer is one of the leading causes of death worldwide. Dendritic cells (DCs) can capture cancer antigens and present them to T lymphocytes, after a maturation process, inducing specific immune responses. Sialyl-Tn (STn) is a tumor-associated carbohydrate antigen that is expressed by several carcinomas. STn downregulates the immune responses towards STn-expressing tumor cells by inducing a tolerogenic phenotype on DCs. For this reason, a successful therapeutic approach against this antigen has to take in consideration the activation of the immune response. The main goal of this thesis was to assess if the use of anti-STn antibodies to block the STn antigen could improve anti-tumor immune responses by reestablishing the mature phenotype on DCs. To do this, STn-expressing cancer cell lines were cultured and DCs were obtained from differentiation of monocytes. Initially, the work comprised the development and characterization of anti-STn antibodies produced by the group through hybridoma technology, using mainly ELISA and flow cytometry. Three hybridoma clones producing IgM anti-STn antibodies were obtained and will be further characterized. A second part of the work included a functional in vitro characterization of humanized anti-STn antibodies. This comprised the establishment of co-cultures between cancer cells and DCs and assessment of the immune response of DCs against STn-expressing cancer cells, with and without STn blockade by those antibodies. The expression of MHC-II and co-stimulatory molecules was assessed by flow cytometry, and the expression of cytokines was assessed by ELISA and RT-PCR. However, the reestablishment of the mature phenotype was not observed. The work developed contributed to understanding that further improvements and assays are necessary; and also that the production of antibodies comprises many variants that can be modified throughout the development and characterization procedures, thus being a long process and needing many optimizations before success can be achieved.